Relationship between Family-Work and Work-Family Conflict with Organizational Commitment and Desertion Intention among Nurses and Paramedical Staff at Hospitals - Nahid Hatam; Marzie Tajik Jalali; Mehrdad Askarian; Erfan Kharazmi (Shiraz University of Medical Sciences, 2016)
Background: High turnover intention rate is one of the most common problems in healthcare organizations throughout the world. There are several factors that can potentially affect the individuals' turnover intention; they include factors such as work-family conflict, family-work conflict, and organizational commitment. The aim of this research was to determine the relationship between family-work and work-family conflicts and organizational commitment and turnover intention among nurses and paramedical staff at hospitals affiliated to Shiraz University of Medical Sciences (SUMS) and present a model using SEM. Methods: This is a questionnaire based cross-sectional study among 400 nurses and paramedical staff of hospitals affiliated to SUMS using a random-proportional (quota) sampling method. Data collection was performed using four standard questionnaires. SPSS software was used for data analysis and SmartPLS software for modeling variables. Results: Mean scores of work-family conflict and desertion intention were 2.6 and 2.77, respectively. There was a significant relationship between gender and family-work conflict (P=0.02). Family-work conflict was significantly higher in married participants (P=0.001). Based on the findings of this study, there was a significant positive relationship between work-family and family-work conflict (P=0.001). Also, work-family conflict had a significant inverse relationship with organizational commitment (P=0.001). An inverse relationship was seen between organizational commitment and turnover intentions (P=0.001). Conclusion: Thus, regarding the prominent and preventative role of organizational commitment in employees' desertion intentions, in order to prevent negative effects of staff desertion in health sector, attempts to make policies to increase people's organizational commitment must be considered by health system managers more than ever.